2006
DOI: 10.1007/s10764-006-9058-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Correlates to Lemur Community Structure in Southeast Madagascar

Abstract: The Fandriana-Marolambo forest corridor is one of the largest (ca. 250,000 ha)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition, conservation planning is urgently needed for the lemurs of Madagascar more generally: many species are threatened by subsistence hunting (Lehman and Wright, 2000), logging, and habitat degradation due to agricultural activities (Johnson & Overdorff, 1999) throughout their ranges. Only 10-20% of the original forest of Madagascar used by many lemur species remains and that in small and fragmented areas (Whitmore, 2000;Ganzhorn, 2001;Lehman et al, 2006;Harper et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, conservation planning is urgently needed for the lemurs of Madagascar more generally: many species are threatened by subsistence hunting (Lehman and Wright, 2000), logging, and habitat degradation due to agricultural activities (Johnson & Overdorff, 1999) throughout their ranges. Only 10-20% of the original forest of Madagascar used by many lemur species remains and that in small and fragmented areas (Whitmore, 2000;Ganzhorn, 2001;Lehman et al, 2006;Harper et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As COMATSA is separated from its neighboring forests only by seasonal roads or footpaths, lemurs can disperse within forest blocks easily by leaping and/or running on tree branches. Lehman et al (2006) reported the ability of some lemur species (e.g., Propithecus sp.) to traverse the open areas between forest fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological variation along geographic clines, including elevation, has been repeatedly established as responsible for differences in morphology and behavior, where organisms become adapted to local conditions along an altitudinal transect (Körner 2007). For example, among primates, a decline in food availability at higher elevations is associated with a decline in group density (Hanya et al 2004;Marshall et al 2005), consumption of a greater proportion of less-preferred foods (Marshall et al 2005), a reduction in species diversity (Lehman et al 2006), and an increase in proportion of time spent feeding (Iwamoto and Dunbar 1983). The colder climate found at higher elevations can also influence cranial morphology (Rae et al 2003) and sleep site selection behaviors (Cui et al 2006).…”
Section: Discussionmentioning
confidence: 99%